Recurrent waning of anti-SARS-CoV-2 neutralizing antibodies despite multiple antigen encounters - Edwards Pradenas; Victor Urrea; Silvia Marfil; Tetyana Pidkova; Carmen Aguilar-Gurrieri; Ferran Abancó; Lourdes Mateu; Anna Chamorro; Eulàlia Grau; Macedonia Trigueros; Jorge Carrillo; Marta Massanella; et al. (Journal of Translational Medicine)
Abstract Background SARS-CoV-2 neutralizing antibodies may protect against symptomatic infection in immunized individuals. However, vaccine-induced antibody levels wane over time, reducing vaccine efficacy. The definition of the waning kinetics of neutralizing SARS-CoV-2 responses and the potential impact of sequential antigen encounters are still poorly defined. Methods Plasma neutralizing activity was determined in longitudinally collected samples from SARS-CoV-2 infected, primo-vaccinated and boosted individuals. Neutralizing activity decay kinetics were modeled against time using Log–Log and biexponential models. Results Neutralizing antibody levels wane after an initial peak in all groups of vaccinated individuals with half-life ranging from 29 to 60 days. Exponential models showed a subsequent stabilization of neutralizing titers to a plateau. Both the peak response and the plateau values depended on vaccine type, infection status and severity of infection. Booster immunization by either vaccines or breakthrough infections did not modify peak, plateau or decay rate values. Conclusions Our results indicate that the waning of SARS-CoV-2 neutralizing antibody responses was recurrent even after several antigen encounters. Repeated immunizations would be required to maintain high levels of neutralizing antibodies and protect vulnerable individuals from symptomatic infection.